2022
DOI: 10.1096/fj.202002588rrr
|View full text |Cite
|
Sign up to set email alerts
|

Laminin N‐terminus α31 expression during development is lethal and causes widespread tissue‐specific defects in a transgenic mouse model

Abstract: Laminins (LMs) are essential components of all basement membranes where they regulate an extensive array of tissue functions. Alternative splicing from the laminin α3 gene produces a non-laminin but netrin-like protein, Laminin N terminus α31 (LaNt α31). LaNt α31 is widely expressed in intact tissue and is upregulated in epithelial cancers and during wound healing. In vitro functional studies have shown that LaNt α31 can influence numerous aspects of epithelial cell behavior via modifying matrix organization, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 108 publications
0
1
0
Order By: Relevance
“…Twenty years have passed since Snead et al identified a novel cell population, integral to the PHM, for which they proposed the term ‘laminocyte’. This name was chosen to highlight both its basement membrane association (of which type IV collagen and laminins are essential structural components) and additionally the laminar pattern of their array entirely within the plane of the detached PHM but absent from the main body of the vitreous gel itself [ 13 , 65 ]. Decades of earlier publications reported the presence of vitreal cells associated with the vitreoretinal interface but failed to classify them morphologically or via immunohistochemistry [ 66 , 67 ].…”
Section: The Laminocytementioning
confidence: 99%
“…Twenty years have passed since Snead et al identified a novel cell population, integral to the PHM, for which they proposed the term ‘laminocyte’. This name was chosen to highlight both its basement membrane association (of which type IV collagen and laminins are essential structural components) and additionally the laminar pattern of their array entirely within the plane of the detached PHM but absent from the main body of the vitreous gel itself [ 13 , 65 ]. Decades of earlier publications reported the presence of vitreal cells associated with the vitreoretinal interface but failed to classify them morphologically or via immunohistochemistry [ 66 , 67 ].…”
Section: The Laminocytementioning
confidence: 99%